Pengaruh Seleksi Karyawan terhadap Kinerja Karyawan di PT. Sultan Kanaka Kreatif Jakarta Timur - Apriyanita Lesmana; Sunan Wibowo; Roni Jarlis (Universitas 45 Surabaya, 2025)
This research is a descriptive quantitative study aimed at analyzing the influence of the selection process on employee performance at PT Sultan Kanaka Kreatif, East Jakarta, as well as measuring the extent of this influence. The sample consisted of 46 employees selected using a saturated sampling technique. The research instrument was a questionnaire comprising 40 statements, divided into two variables: the Selection variable and the Employee Performance variable. Data analysis was conducted using multiple linear regression, with t-tests and the coefficient of determination (R Square), through SPSS software version 22. Based on the results of the data analysis, the Selection variable had a significance value of 0.000, which is smaller than the significance level of 0.05. This indicates that, partially, the Selection variable has a significant influence on Employee Performance at PT Sultan Kanaka Kreatif. Thus, it can be concluded that the company's selection process makes a tangible contribution to improving employee performance. The influence of the Selection variable on Employee Performance was found to be 54.2%, meaning that more than half of the changes in employee performance can be explained by the effectiveness of the selection process implemented by the company. Meanwhile, the remaining 45.8% is influenced by other factors not discussed in this study, such as training, work motivation, work environment, leadership, non-selection-related relationships, and other external factors.